Tree pollen representation in surface pollen assemblages from different vegetation zones of European Russia - Novenko, Elena; Mazei, Natalia; Kusilman, Maria (Ecological Questions, 2017)
The paper presents the results of studies of 270 modern pollen assemblages from different vegetation zones of the East European plain. According to obtained data the ratio of the main components in pollen assemblages from forest and forest-steppe localities is characterized by higher proportion of the regional components (e.g., Betula, Alnus, Pinus) and significantly lower participation of Picea pollen and one of deciduous trees then the proportions of these species in the surrounding vegetation. Steppe vegetation is determined by higher share of non- arboreal pollen and specific floristic composition. The comparison between geographical range of tree species and maps showing distribution of their pollen show a possibility a long distance transfer of Carpinus and Fagus pollen while pollen of Quercus and Tilia occurred close to their modern geographical ranges.